Biochemical and Physiological Effects of Food-Induced Gastro-Esophageal Reflux Disease (GERD) in our Population. A Comparative Clinical Study - Kamran Arzoo, Amna Akram, Awais Anwar, Rizwana Hussain, Saba Shuja Shaikh, Marium Munir Tunio (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gastroesophageal reflux disease (GERD) can lead to significant medical complications such as esophageal ulcerations, peptic stenosis and esophageal adenocarcinoma. Aims and Objectives: The aims and objectives of current study was to evaluate the biochemical and physiological parameters associated with daily food which caused gastroesophageal reflux disease in population of Pakistan. Study Design: This was a comparative clinical study designed to investigate the effect of different dietary interventions on the symptoms of gastroesophageal reflux disease (GERD). Statistical analysis: Raw data was analyzed by using SPSS software (version 26.0). Descriptive statistics were used to summarize demographic and clinical characteristics of the study population. Methodology: A total of 100 adult patients with confirmed GERD diagnosis were randomized to either a standard GERD diet. The primary outcome measure was the change in GERD symptom severity, as assessed by the Gastroesophageal Reflux Disease Questionnaire (GERDQ) score after 12 weeks of dietary intervention. Secondary outcome measures included changes in esophageal inflammation, measured by endoscopy, and patient-reported improvement in quality of life. Practical Implications: Current study focuses on evaluation of the biochemical and physiological parameters associated with daily food which caused gastroesophageal reflux disease in population of Pakistan which will spread awareness among community for the prevention of GERD. Results: Demographic characteristics of the study population are presented in Table 1. The mean age of the patients was 48.7 years, and there were slightly more females (60%) than males (40%). The majority of patients (60%) reported a history of smoking, and 10% reported regular alcohol consumption. There was a significant (P≤0.05) difference between the two groups with respect to age, sex, smoking history and alcohol consumption. The findings of this study suggest that dietary interventions, particularly a modified Mediterranean diet, can significantly improve the symptoms and quality of life of patients with GERD. Conclusion: In conclusion, our study found that a modified Mediterranean diet may be more effective than a standard GERD diet in reducing the severity of GERD symptoms and improving quality of life in patients with GERD. This was evidenced by a significantly greater reduction in GERD score in Group B compared to Group A, as well as a higher proportion of patients reporting improved quality of life in Group B. In addition, the incidence of esophageal inflammation was lower in Group B, although this difference was not statistically significant. Keywords: dietary intervention, Mediterranean diet, symptom severity, quality of life, esophageal inflammation,